KEBIJAKAN PRESIDEN BRAZIL TERHADAP PERENCANAAN PENGEMBANGAN WILAYAH PERTANIAN DI HUTAN AMAZON YANG MENGANCAM “HUMAN SECURITY” MASYARAKAT BRAZIL - Intan Rodiah (UIR Press, 2019)
Amazon forest in Brazil is one of the lungs of the world and a source of oxygen, especially in the South American region. Under the leadership of President Bolsonaro, there have been many cases of forest fires and illegal deforestation due to the weakening of environmental protection in the Amazon forest region. This study wants to analyze the Brazilian president's policy towards developing agricultural areas in the Amazon forest. This paper uses a literature study writing system by taking resources from several references such as books, journals, articles, news and other sources related to the author's research. This research uses descriptive analytic method. Many things that arise due to the Amazon forest fires, especially regarding the